Neuroprotective effects of phenylacetylglycine via β2AR on cerebral ischemia/reperfusion injury in rats - Wenjie Hu; Xueyan Kuang; Yao Zhang; Yimin Luo; Litao Zhang (Saudi Pharmaceutical Journal)
Phenylacetylglycine (PAGly) is a small molecule derived from phenylalanine in the gut via glycine degradation and conjugation. It has been associated with both the progression of atherosclerosis and protective effects on the myocardium. This study evaluated the function and the underlying mechanisms of PAGly in a rat cerebral ischemia/reperfusion (I/R) injury model. The results indicated that PAGly markedly alleviated cerebral infarct volume (P = 0.0024) and improved the neurobehavioral outcomes (P = 0.0149) after I/R injury. PAGly is structurally analogous to catecholamines and binds to β2-adrenergic receptors (β2AR) on microglia without altering the expression of these receptors (P = 0.9137), but instead inhibiting their activity. It was also observed that when β2AR was engaged in microglia, PAGly suppressed the release of TNF-α (P = 0.0018), IL-1β (P = 0.0310), and IL-6 (P = 0.0017), thereby reducing neuronal apoptosis (P = 0.000003). Furthermore, the protective effect of PAGly diminished after the administration of β2AR-specific agonist fenoterol (P = 0.0055). These data indicate that PAGly mitigates cerebral I/R injury by inhibiting microglial inflammation via β2AR, highlighting its potential as a therapeutic agent. These findings position PAGly as a promising candidate for therapeutic intervention in cerebrovascular injuries, warranting further exploration in clinical settings.